2023
DOI: 10.1002/ejhf.2894
|View full text |Cite
|
Sign up to set email alerts
|

Patient phenotype profiling in heart failure with preserved ejection fraction to guide therapeutic decision making. A scientific statement of the Heart Failure Association, the European Heart Rhythm Association of the European Society of Cardiology, and the European Society of Hypertension

Abstract: Heart failure with preserved ejection fraction (HFpEF) represents a highly heterogeneous clinical syndrome affected in its development and progression by many comorbidities. The left ventricular diastolic dysfunction may be a manifestation of various combinations of cardiovascular, metabolic, pulmonary, renal, and geriatric conditions. Thus, in addition to treatment with sodium–glucose cotransporter 2 inhibitors in all patients, the most effective method of improving clinical outcomes may be therapy tailored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 224 publications
0
35
0
8
Order By: Relevance
“…Heart failure (HF) with preserved ejection fraction (HFpEF) is a heterogeneous syndrome 1–3 . A scientific statement from the Heart Failure Association (HFA) described most common HFpEF phenotypes, related comorbidities and treatment options for each phenotype 4 …”
Section: Heart Failure With Preserved Ejection Fractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heart failure (HF) with preserved ejection fraction (HFpEF) is a heterogeneous syndrome 1–3 . A scientific statement from the Heart Failure Association (HFA) described most common HFpEF phenotypes, related comorbidities and treatment options for each phenotype 4 …”
Section: Heart Failure With Preserved Ejection Fractionmentioning
confidence: 99%
“…1-3 A scientific statement from the Heart Failure Association (HFA) described most common HFpEF phenotypes, related comorbidities and treatment options for each phenotype. 4 Exercise testing has a key role in the diagnosis and prognostic assessment of HFpEF. 1,5,6 In a study by Alogna et al, 7 398 patients with HFpEF undergoing comprehensive echocardiography and invasive cardiopulmonary exercise testing were categorized low versus preserved biventricular cardiac power output (BCPO) reserve (< vs ≥ median of 1.57 W).…”
mentioning
confidence: 99%
“…10-13 Among them, obesity is common and may define a specific one. [10][11][12] Chin et al 14 showed that increased epicardial adipose tissue thickness is associated with subclinical cardiac dysfunction in subjects with severe obesity and no known history of cardiovascular (CV) disease, referred to bariatric surgery.…”
Section: Pathophysiologymentioning
confidence: 99%
“…10-13 Among them, obesity is common and may define a specific one. [10][11][12] Chin et al 14 showed that increased epicardial adipose tissue thickness is associated with subclinical cardiac dysfunction in subjects with severe obesity and no known history of cardiovascular (CV) disease, referred to bariatric surgery.Degenerative aortic valve stenosis (AVS) with preserved ejection fraction (EF) might represent a specific sub-phenotype of HFpEF. In a prospective study, 148 patients with HFpEF, 150 patients with degenerative moderate-to-severe AVS with preserved EF and 66 age-and sex-matched healthy controls underwent functional capacity measurements.…”
mentioning
confidence: 99%
“…It may also explain why it may be difficult to improve quality of life using HF-targeted therapies alone, particularly in patients with HFpEF who have a higher burden of comorbidities. 26 Notably, the comorbidities associated with the highest impact on KCCQ scores, anaemia, angina, chronic obstructive pulmonary disease and obesity, in both HFrEF and HFpEF, are 'treatable' comorbidities, 27 demonstrating the potential of their treatment to improve health status in patients with HF.…”
mentioning
confidence: 99%